The effects of cluster-set and traditional-set postactivation potentiation protocols on vertical jump performance - Dello Lacono, A.; Beato, M.; Halperin, I. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To compare the effects of 2 postactivation potentiation (PAP) protocols using traditional-set or cluster-set configurations on countermovement jump performance. Methods: Twenty-six male basketball players completed 3 testing sessions separated by 72 hours. On the first session, subjects performed barbell jump squats with progressively heavier loads to determine their individual optimum power load. On the second and third sessions, subjects completed 2 PAP protocols in a randomized order: 3 sets of 6 repetitions of jump squats using optimum power load performed with either a traditional-set (no interrepetition rest) or a cluster-set (20-s rest every 2 repetitions) configuration. After a warm-up, countermovement jump height was measured using a force platform before, 30 seconds, 4 minutes, and 8 minutes after completing the PAP protocols. The following kinetic variables were also analyzed and compared: relative impulse, ground reaction force, eccentric displacement, and vertical leg-spring stiffness. Results: Across both conditions, subjects jumped lower at post 30 seconds by 1.21 cm, and higher in post 4 minutes by 2.21 cm, and in post 8 minutes by 2.60 cm compared with baseline. However, subjects jumped higher in the cluster condition by 0.71 cm (95% confidence interval, 0.37 to 1.05 cm) in post 30 seconds, 1.33 cm (95% confidence interval, 1.02 to 1.65 cm) in post 4 minute, and 1.64 cm (95% confidence interval, 1.41 to 1.88 cm) in post 8 minutes. The superior countermovement jump performance was associated with enhanced kinetic data. Conclusions: Both protocols induced PAP responses in vertical jump performance using jump squats at optimum power load. However, the cluster-set configuration led to superior performance across all time points, likely due to reduced muscular fatigue.